PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK BERBANTUAN MEDIA QUESTION BOX TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV UPT SPF SD INPRES BTN IKIP 1 MAKASSAR - Asti Arfah; Abdul Rahman; Rahmawati Patta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low achievement in mathematics. The main objectives of this research were to determine (1) the effect of the cooperative learning model of the Talking Stick type assisted by the Question Box media on the mathematics learning outcomes of fourth-grade students at SD INPRES BTN IKIP 1 Makassar, and (2) the perceptions of fourth-grade students at SD INPRES BTN IKIP 1 Makassar regarding the implementation of the cooperative learning model of the Talking Stick type assisted by the Question Box media in mathematics learning. The study used a quantitative approach with a quasi-experimental design of the Nonequivalent Post-test Only Control Group type. The research subjects consisted of 49 students divided into an experimental group (IV A) and a control group (IV B) through purposive sampling. Data were collected through tests, questionnaires, and documentation, then analyzed using descriptive and inferential statistics. The independent sample t-test yielded a p-value of 0.002 < 0.05, indicating that H₀ was rejected, meaning there was a significant difference between the experimental and control groups. In addition, the results of the student perception questionnaire showed that students’ perceptions were categorized as very good (76%) and good (24%). Thus, it can be concluded that the model of the Talking Stick type assisted by the Question Box media has a significant effect on the mathematics learning outcomes of fourth-grade students at SD INPRES BTN IKIP 1 Makassar, and students have a positive perception of the cooperative learning model of the Talking Stick type assisted by the Question Box media.